2017
DOI: 10.1159/000464125
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fibrosis Effect of Relaxin and Spironolactone Combined on Isoprenaline-Induced Myocardial Fibrosis in Rats via Inhibition of Endothelial–Mesenchymal Transition

Abstract: Background: The effect of relaxin and spironolactone combined on myocardial fibrosis has not been reported. Thus, we investigated the effect of the combined therapy on isoprenaline-induced myocardial fibrosis and the mechanism. Methods: Rats were injected subcutaneously with isoprenaline to induce myocardial fibrosis and underwent subcutaneous injection with relaxin (2 µg·kg-1·d-1) and given a gavage of spironolactone (30 mg·kg-1·d-1) alone or combined for 14 days. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The cardiac performance (+dP/dt max and −dP/dt max ) in the normal rats indicated responses consistent to a previous report [ 24 ]. Furthermore, the cardiac performance significantly decreased in the diabetic rats compared with the normal rats, and Rh2 treatment restored the dP/dt max in the diabetic rats ( Table 1 ).…”
Section: Resultssupporting
confidence: 91%
“…The cardiac performance (+dP/dt max and −dP/dt max ) in the normal rats indicated responses consistent to a previous report [ 24 ]. Furthermore, the cardiac performance significantly decreased in the diabetic rats compared with the normal rats, and Rh2 treatment restored the dP/dt max in the diabetic rats ( Table 1 ).…”
Section: Resultssupporting
confidence: 91%
“…EndMT is a type of EMT (Epithelial-mesenchymal transition) that specifically refers to vascular/cardiac endothelial cells undergoing mesenchymal transition [12, 36-39], which contributes to angiopoiesis and pathological fibrosis mainly in human vascular diseases [40]. EndMT can be induced by multiple factors via several interactive signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cardiac myofibroblasts, serelaxin also inhibited TGF-β1-induced mobility of endothelial cells through a Notch-1-dependent pathway, and increased expression of CD31 while decreasing vimentin content of human umbilical vein endothelial cells (HUVECs) in vitro (Zhou et al, 2015). In a separate study, serelaxin was capable of reducing cardiac fibrosis in vivo via the inhibition of EndMT, and by increasing VE-cadherin and CD31 levels while suppressing vimentin and α-SMA levels in HUVECs in vitro (Cai et al, 2017). While these combined findings suggest that relaxin inhibits myofibroblast-mediated aberrant ECM synthesis and deposition at multiple levels, further studies are required to fully understand the detailed mechanisms underlying its potent antifibrotic actions in various tissues and organs for future therapeutic applications.…”
Section: Relaxin Effects On Endothelial-to-mesenchymal Transitionmentioning
confidence: 92%
“…Recent studies showed that serelaxin inhibits EndMT within the heart and kidney of isoprenaline-induced cardiomyopathy in rodents (Cai et al, 2017;Zheng et al, 2017). Zhou et al found that serelaxin improves cardiac function in rats with myocardial fibrosis, by reducing EndMT and interstitial collagens I and III, while increasing the microvascular density of the heart (Zhou et al, 2015).…”
Section: Relaxin Effects On Endothelial-to-mesenchymal Transitionmentioning
confidence: 99%